2017
DOI: 10.22146/ipas.10827
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Attitude, Subjective Norm, and Perceived Behavioural Control Toward Snack Consumer Behaviour in Halal Labeling in Yogyakarta

Abstract: Halal label was not only related to substances forbidden for a particular religion, but was also associated with many other important things. The talk about halal label issue also meant a talk about health and hygiene. This research aimed to determine the learning level of consumer of the concept of halal-labeled snack; to know how to influence learning, attitudes, subjective norms, perceived behavioural control, and the prices on consumer behaviour of packaged halal-labeled snack, either partially or simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The findings of this study prove that perceived behavioral control is very important in explaining the use of online shopping during the covid outbreak. The findings of this study are in line with the study conducted by previous researchers (e:g: Afsari et al, 2017;Bandara & Amarasena, 2018;Noor et al, 2019). The findings of this study are very useful to service providers and stakeholders in developing an online shopping system.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of this study prove that perceived behavioral control is very important in explaining the use of online shopping during the covid outbreak. The findings of this study are in line with the study conducted by previous researchers (e:g: Afsari et al, 2017;Bandara & Amarasena, 2018;Noor et al, 2019). The findings of this study are very useful to service providers and stakeholders in developing an online shopping system.…”
Section: Discussionsupporting
confidence: 90%
“…Health reasons have a positive and significant effect on halal concern for Generation Z Indonesian Muslims by producing a standardized coefficient (β) of 0.784 and a p-value < 0.001. Healthy and clean food is often associated with food that has received a halal label (Afsari et al, 2017). Muslims believe that consuming halal food is not only an obligation to carry out religious orders but it also affects their physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars also claimed that attitude plays a huge role in impacting the consumers' intention to purchase Halal products. Afsari, Suryantini, & Mulyo (2017) conducted a consumer behavior study towards the Halal-certified snacks in Yogyakarta and attitude was found to have a strong relationship with the intention to purchase. Suki and Salleh (2016) also indicated that attitude has a very important role in predicting the consumer's intention to patronize Halal stores.…”
Section: Attitudementioning
confidence: 99%